2018
DOI: 10.3389/fnagi.2018.00003
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological Approaches for Dementia Therapy and Significance of Natural Products and Herbal Drugs

Abstract: Dementia is a clinical syndrome wherein gradual decline of mental and cognitive capabilities of an afflicted person takes place. Dementia is associated with various risk factors and conditions such as insufficient cerebral blood supply, toxin exposure, mitochondrial dysfunction, oxidative damage, and often coexisting with some neurodegenerative disorders such as Alzheimer's disease (AD), Huntington's disease (HD), and Parkinson's disease (PD). Although there are well-established (semi-)synthetic drugs currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 259 publications
1
75
0
Order By: Relevance
“…At the present time, there is growing worldwide use of herbal medicines for preventive and therapeutic applications based on historical knowledge. In connection with the aforementioned mechanism of glutamate-induced oxidative toxicity, medicinal plants or naturally derived compounds with antioxidant and antiapoptotic effects are currently being researched as neuroprotective agents [ 15 19 ]. Acanthus ebracteatus Vahl.…”
Section: Introductionmentioning
confidence: 99%
“…At the present time, there is growing worldwide use of herbal medicines for preventive and therapeutic applications based on historical knowledge. In connection with the aforementioned mechanism of glutamate-induced oxidative toxicity, medicinal plants or naturally derived compounds with antioxidant and antiapoptotic effects are currently being researched as neuroprotective agents [ 15 19 ]. Acanthus ebracteatus Vahl.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that G. glabra extract is useful in improving the capacity for learning; however, its dose should be closely determined to inhibit the depressant effectiveness. Moreover, diammonium-glycyrrhizinate inhibited the cognitive and mitochondrial malfunctions caused by Aβ42 in vivo [101]. In conclusion, Glycyrrhiza extracts exhibit antioxidative and anti-inflammatory potential, and they regulate glutamate signaling and apoptosis.…”
Section: In Vivo Pharmacological/biological Properties Of G Glabra Ementioning
confidence: 82%
“…They showed great learning and memory enhancement efficacy in mice; however, its mode of action is not clear yet [100]. The oral administration of another Glycyrrhiza species, G. glabra extract, was reported to enhance the learning ability of mice [101]. This indicates that G. glabra extract is useful in improving the capacity for learning; however, its dose should be closely determined to inhibit the depressant effectiveness.…”
Section: In Vivo Pharmacological/biological Properties Of G Glabra Ementioning
confidence: 99%
“…[ 104 , 105 ]. Numerous studies have reported a beneficial effect of polyphenols in the prevention of some diseases: ischemic heart diseases, Alzheimer’s disease, diabetes, liver disorders, allergies, bowel diseases and more [ 106 , 107 , 108 , 109 , 110 ]. Polyphenols have strong antioxidant properties related to free radical scavenging activity, chain-braking oxidation pathway activity and metal-chelating activity [ 111 , 112 , 113 , 114 ].…”
Section: Functional Compounds With Relevance For Meat Industrymentioning
confidence: 99%